Model Pembelajaran Berbasis Teknologi untuk Pengembangan Profesionalisme Pengajar Teologi - Kalatiku, Matius; Christofer Cahyad; Djuwansah Suhendro P Stephanus; Lia Lesty S; Lidiawati Lidiawati (Sekolah Tinggi Teologia Kerusso Indonesia, 2023)
This study aims to develop a technology-based learning model that can support the improvement of the professionalism of theology teachers. In today's digital era, the mastery of technology by teachers is increasingly important to ensure the effectiveness of the learning process. The model developed integrates technology in various aspects, from training needs analysis, selection of technology platforms, to the implementation of technology-based curriculum. The learning process using technology, such as Learning Management System (LMS), video conferencing, and cloud-based applications, is designed to strengthen teachers' abilities in managing digital classes and delivering materials interactively and effectively. Evaluation is carried out through monitoring teacher involvement, student learning outcomes, and improving teachers' technological skills. The results show that the implementation of this model significantly improves pedagogical skills, digital literacy, and teaching effectiveness. Thus, this technology-based learning model makes an important contribution to the development of the professionalism of theology teachers amidst the challenges of globalization and digitalization in education.